Explaining financial scandals : corporate governance, structured finance and the enlightened sovereign control paradigm - Bavoso, Vincenzo (Cambridge Scholars Publishing, 2012)
The explosion of the global financial crisis in 2007-08 reignited the urgency to reflect on the origins and causes of financial collapses. As the events in the above period triggered an economic meltdown that is still ongoing, comparisons with the Great Crash of 1929 started to abound. In particular, the externalities that a broad spectrum of societal groups had to bear as a consequence of various banking failures highlighted the necessity of a more inclusive and balanced regulation of firms ...